KEBIJAKAN PENGEMBANGAN OBJEK WISATA DANAU KAYANGAN KOTA PEKANBARU TAHUN 2010-2012 - Hrp, Anggi Rahmawati; Amin, Raja Muhammad Amin Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study took reasons Kayangan Lake City is due to Kayangan Lake potentially have a wide area so that it can be developed better with the natural conditions are still beautiful to be developed compared to other attractions in the city of Pekanbaru available.The purpose of this study to determine the Development Implementation Kayangan Lake City Attractions Pekanbaru and to determine the barriers Development Kayangan Lake City Attractions Pekanbaru.The location of this research is precisely in Pekanbaru City Tourism Office conducting Kayangan Lake tourism development policy by reason of the slow development of the tourist area of Kayangan Lake .Policy Development Kayangan Lake City Attractions Pekanbaru assessed potential .Key : Policy , Development , Department of Tourism